2012
DOI: 10.1002/cctc.201200065
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalyzed Isomerization of α‐Substituted Alkynoates into Trisubstituted Allenoates by Dynamic Kinetic Resolution

Abstract: The left hand claps the right: Highly enantioselective isomerization of racemic α‐substituted alkynoates into nonracemic trisubstituted allenoates was achieved through the catalytic dynamic kinetic resolution mediated by bifunctional benzothiadiazine. This reaction proceeded with good conversion and high enantioselectivity to give the desired allenoates in good yields without recovering the significant amounts of starting materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 47 publications
1
40
0
Order By: Relevance
“…When α-substituted 3-butynoates 15 [37] are similarly treated with the bifunctional catalysts, the corresponding trisubstituted allenoesters 16 would be obtained via 1,3-proton migration [9]. However, such an asymmetric reaction has not been reported yet.…”
Section: Isomerization Of α-Substituted 3-butynoates Via Dynamic Kinementioning
confidence: 99%
See 2 more Smart Citations
“…When α-substituted 3-butynoates 15 [37] are similarly treated with the bifunctional catalysts, the corresponding trisubstituted allenoesters 16 would be obtained via 1,3-proton migration [9]. However, such an asymmetric reaction has not been reported yet.…”
Section: Isomerization Of α-Substituted 3-butynoates Via Dynamic Kinementioning
confidence: 99%
“…Therefore, there have been so far many reports on the asymmetric synthesis of optically active allenes [27,28]. Among them, we focused on the base-catalyzed isomerization of alkynylesters into allenoesters from the atom-economical perspective [8,9,[29][30][31]. …”
Section: Isomerization Of Alkynoates To Allenoatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports [3b,c] showed that ligands could accelerate the reaction. [9] Herein, we report the first asymmetric C À H insertion between terminal alkynes and a-diazoesters in the presence of cost-efficient copper(I) salts and chiral guanidinium salts.V arious trisubstituted chiral allenoates were afforded directly in high yield and enantioselectivity under mild reaction conditions.Some experiments were carried out to probe into the reaction mechanism. Path Aw ould involve CÀHi nsertion to form ac hiral organocopper intermediate,w hich could be protonated enantioselectively to give the chiral allenoates.Alternatively,the reaction could proceed by cooperative catalysis.C opper salts could accelerate the formation of an alkynoate precursor (path B), followed by the guanidine catalyst serving as achiral base to facilitate the enantioselective isomerization to the final allenoates (path C).…”
mentioning
confidence: 98%
“…[5] They are also found in many natural products [6] and as backbones of chiral ligands in asymmetric catalysis. [8] Nevertheless,t he catalytic asymmetric synthesis of axially chiral allenes,especially starting from prochiral substrates,is still in its infancy.T he asymmetric isomerization of the FG-CH 2 ÀCCm oiety by chiral base catalysts,s uch as guanidines, [9] were among the early examples.R ecently,s ome ingenious asymmetric protocols for the synthesis of chiral allenes,i ncluding the kinetic resolution of racemic allenoates, [10a] functionalization of 1-alkyl allene-1,3-dicarboxylates, [10b] b-hydride elimination of enoltriflates, [10c] carbonylation of propargylic carbonates, [10d] and addition to activated enynes, [10e] were reported by the groups of Gong, Maruoka, Frantz, Ma, and Zhang,respectively. [8] Nevertheless,t he catalytic asymmetric synthesis of axially chiral allenes,especially starting from prochiral substrates,is still in its infancy.T he asymmetric isomerization of the FG-CH 2 ÀCCm oiety by chiral base catalysts,s uch as guanidines, [9] were among the early examples.R ecently,s ome ingenious asymmetric protocols for the synthesis of chiral allenes,i ncluding the kinetic resolution of racemic allenoates, [10a] functionalization of 1-alkyl allene-1,3-dicarboxylates, [10b] b-hydride elimination of enoltriflates, [10c] carbonylation of propargylic carbonates, [10d] and addition to activated enynes, [10e] were reported by the groups of Gong, Maruoka, Frantz, Ma, and Zhang,respectively.…”
mentioning
confidence: 99%